2022
DOI: 10.3389/fcell.2022.852244
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 Protects Skin From Ultraviolet B -Induced Photodamage by Regulating Autophagy and Reactive Oxygen Species Production

Abstract: Ultraviolet (UV) irradiation has been well documented to be linked with almost all skin problems we know, and both dermis and epidermis may be affected to varying degrees by UV irradiation. Every time when exposed to sunlight without protection, our skin will step closer to photoaging, leading to irreversible consequences ultimately. Heat shock protein 27 (HSP27) is a vital protein involved in cell growth, autophagy, apoptosis, drug resistance, tumor genesis and metastasis. Evidence suggests that the organism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The experimental results in this study also con rmed this view. According to the previous ndings of our group, the protein expression level of Hsp27 was not signi cantly altered in UVB-induced photodamage models of epidermal keratin-forming cells and dermal broblasts, while its phosphorylated form, P-Hsp27, was signi cantly elevated and activated autophagy (12). Similar results were achieved in the experiments in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The experimental results in this study also con rmed this view. According to the previous ndings of our group, the protein expression level of Hsp27 was not signi cantly altered in UVB-induced photodamage models of epidermal keratin-forming cells and dermal broblasts, while its phosphorylated form, P-Hsp27, was signi cantly elevated and activated autophagy (12). Similar results were achieved in the experiments in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Small heat shock protein 27 (Hspb2), a new member of the heat shock protein family, is highly represented in heart and skeletal muscle (11). Previous studies by our group have also shown that Hsp27 can protect the skin from UVB-induced photodamage by mediating autophagy and the production of reactive oxygen species (12). Rapamycin, a speci c inhibitor of mTOR, has been shown in many studies, both in vivo and in vitro, to have an important role in delaying aging and treating age-related diseases (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…HSP27 may delay the process of atherosclerosis by inhibiting mitochondrial apoptosis pathway and reducing the level of reactive oxygen species(ROS) [17,23]. Meanwhile HSP27 can regulate apoptosis and autophagy, which plays an antiatherosclerotic role [24,25]. ShiC et al found that HSP27 inhibited cholesterol uptake by macrophages through down-regulated the expression of scavenger receptor-A (SR-A) in macrophages via NF-κ B pathway, and thus reduced the transformation of macrophages into foam cells[8].…”
Section: Discussionmentioning
confidence: 99%
“…Many signaling proteins are known to be involved in the apoptosis of prostate cancer cells. Heat shock protein 27 (HSP27) is a cell survival factor synthesized in response to stress, such as UV irradiation, oxidizing agents, inflammation, hypoxia, and tumors [ 9 , 10 , 11 ]. In the absence of stress, HSP27 plays an important role in maintaining cellular homeostasis as a molecular chaperone that folds, assembles, and transports polypeptides.…”
Section: Introductionmentioning
confidence: 99%